AN ANALYSIS OF MASLOW’S HIERARCHY OF NEED IN THE GREAT GATSBY NOVEL BY FRANCISS SCOTT FITZGERALD’S - Ritna Bahuwa (Universitas Muhammadiyah Gorontalo, 2018)
This research discussed the main character’s need, Jay Gatsby. Namely, psychological needs, safety needs, love, and belonging need, Esteem needs, and actualization need. The objective of this research is to analyze the Abraham Maslow’s hierarchy need described in the Gatsby novel by Francis Scott Key Fitzgerald. This research used a descriptive qualitative method and Abraham Maslow’s theory. The result of this research was found from five types of Abraham Maslow’s need, there were two types that were not fulfilled by Jay Gatsby, namely safety needs, and love and belongingness need so, that actualization needs could not be reached.Keywords: Jay Gatsby, Abraham Maslow’s Hierarchy of Needs